2008
DOI: 10.1080/00365510802409703
|View full text |Cite
|
Sign up to set email alerts
|

Order of magnitude differences between methods for maintaining physiological 17β‐oestradiol concentrations in ovariectomized rats

Abstract: The use of animal, especially rat, models, is crucial for elucidating the biological effects and mechanisms of the widely used hormone 17β-estradiol. Unfortunately there is a lack of consensus on optimal means of obtaining and maintaining physiological 17β-estradiol concentrations in plasma.This may be the reason for varying results in several studies including the disagreement on whether 17β-estradiol is neuroprotective or not. Very few studies have been devoted to investigating the characteristics and biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
72
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 34 publications
9
72
2
Order By: Relevance
“…However, this hypothesis is not corroborated by the current review because no relationship was found between the effects of estrogens and the washout period. Also, in a previous study in our laboratory, we found that the duration of the washout period did not influence the later induced plasma concentrations (Strom et al, 2008).…”
Section: Earlier Reviews and Theoriessupporting
confidence: 46%
See 3 more Smart Citations
“…However, this hypothesis is not corroborated by the current review because no relationship was found between the effects of estrogens and the washout period. Also, in a previous study in our laboratory, we found that the duration of the washout period did not influence the later induced plasma concentrations (Strom et al, 2008).…”
Section: Earlier Reviews and Theoriessupporting
confidence: 46%
“…It has been shown that the pellets are unreliable considering what is stated about the dosage in relation to the actual plasma levels produced (Strom et al, 2008). The hypothesis presented in the current paper, that estrogen is related to ischemic damage in a biphasic-or even more complex-manner does not presume that the dose-response curve in any specific interval along the dose axis is perfectly linear.…”
Section: Increased Neurologic Damage Related To Use Of Slow-release Pmentioning
confidence: 68%
See 2 more Smart Citations
“…This is crucial since the 17β-estradiol level/administration method profoundly influences the experimental results 1-3 . We have in a series of studies characterized the different modes of 17β-estradiol administration, finding that subcutaneous silastic capsules and per-oral nut-cream Nutella are superior to commercially available slow-release pellets (produced by the company Innovative Research of America) and daily injections in terms of producing physiological serum concentrations of 17β-estradiol [4][5][6] . Amongst the advantages of the nut-cream method, that previously has been used for buprenorphine administration 7 , is that when used for estrogen administration it resembles peroral hormone replacement therapy and is non-invasive.…”
mentioning
confidence: 99%